Using the Collatz Conjecture, show how we get to "oneness" from 27 in 111 steps.

We start with n = 27

## Step *1* of 111 → n = 27

Since 27 is odd, we take 3(27) + 1 → 81 + 1 = 82

## Step *2* of 111 → n = 82

Since 82 is even, we divide by 2 to get 82 ÷ 2 = 41

## Step *3* of 111 → n = 41

Since 41 is odd, we take 3(41) + 1 → 123 + 1 = 124

## Step *4* of 111 → n = 124

Since 124 is even, we divide by 2 to get 124 ÷ 2 = 62

## Step *5* of 111 → n = 62

Since 62 is even, we divide by 2 to get 62 ÷ 2 = 31

## Step *6* of 111 → n = 31

Since 31 is odd, we take 3(31) + 1 → 93 + 1 = 94

## Step *7* of 111 → n = 94

Since 94 is even, we divide by 2 to get 94 ÷ 2 = 47

## Step *8* of 111 → n = 47

Since 47 is odd, we take 3(47) + 1 → 141 + 1 = 142

## Step *9* of 111 → n = 142

Since 142 is even, we divide by 2 to get 142 ÷ 2 = 71

## Step *10* of 111 → n = 71

Since 71 is odd, we take 3(71) + 1 → 213 + 1 = 214

## Step *11* of 111 → n = 214

Since 214 is even, we divide by 2 to get 214 ÷ 2 = 107

## Step *12* of 111 → n = 107

Since 107 is odd, we take 3(107) + 1 → 321 + 1 = 322

## Step *13* of 111 → n = 322

Since 322 is even, we divide by 2 to get 322 ÷ 2 = 161

## Step *14* of 111 → n = 161

Since 161 is odd, we take 3(161) + 1 → 483 + 1 = 484

## Step *15* of 111 → n = 484

Since 484 is even, we divide by 2 to get 484 ÷ 2 = 242

## Step *16* of 111 → n = 242

Since 242 is even, we divide by 2 to get 242 ÷ 2 = 121

## Step *17* of 111 → n = 121

Since 121 is odd, we take 3(121) + 1 → 363 + 1 = 364

## Step *18* of 111 → n = 364

Since 364 is even, we divide by 2 to get 364 ÷ 2 = 182

## Step *19* of 111 → n = 182

Since 182 is even, we divide by 2 to get 182 ÷ 2 = 91

## Step *20* of 111 → n = 91

Since 91 is odd, we take 3(91) + 1 → 273 + 1 = 274

## Step *21* of 111 → n = 274

Since 274 is even, we divide by 2 to get 274 ÷ 2 = 137

## Step *22* of 111 → n = 137

Since 137 is odd, we take 3(137) + 1 → 411 + 1 = 412

## Step *23* of 111 → n = 412

Since 412 is even, we divide by 2 to get 412 ÷ 2 = 206

## Step *24* of 111 → n = 206

Since 206 is even, we divide by 2 to get 206 ÷ 2 = 103

## Step *25* of 111 → n = 103

Since 103 is odd, we take 3(103) + 1 → 309 + 1 = 310

## Step *26* of 111 → n = 310

Since 310 is even, we divide by 2 to get 310 ÷ 2 = 155

## Step *27* of 111 → n = 155

Since 155 is odd, we take 3(155) + 1 → 465 + 1 = 466

## Step *28* of 111 → n = 466

Since 466 is even, we divide by 2 to get 466 ÷ 2 = 233

## Step *29* of 111 → n = 233

Since 233 is odd, we take 3(233) + 1 → 699 + 1 = 700

## Step *30* of 111 → n = 700

Since 700 is even, we divide by 2 to get 700 ÷ 2 = 350

## Step *31* of 111 → n = 350

Since 350 is even, we divide by 2 to get 350 ÷ 2 = 175

## Step *32* of 111 → n = 175

Since 175 is odd, we take 3(175) + 1 → 525 + 1 = 526

## Step *33* of 111 → n = 526

Since 526 is even, we divide by 2 to get 526 ÷ 2 = 263

## Step *34* of 111 → n = 263

Since 263 is odd, we take 3(263) + 1 → 789 + 1 = 790

## Step *35* of 111 → n = 790

Since 790 is even, we divide by 2 to get 790 ÷ 2 = 395

## Step *36* of 111 → n = 395

Since 395 is odd, we take 3(395) + 1 → 1185 + 1 = 1186

## Step *37* of 111 → n = 1186

Since 1186 is even, we divide by 2 to get 1186 ÷ 2 = 593

## Step *38* of 111 → n = 593

Since 593 is odd, we take 3(593) + 1 → 1779 + 1 = 1780

## Step *39* of 111 → n = 1780

Since 1780 is even, we divide by 2 to get 1780 ÷ 2 = 890

## Step *40* of 111 → n = 890

Since 890 is even, we divide by 2 to get 890 ÷ 2 = 445

## Step *41* of 111 → n = 445

Since 445 is odd, we take 3(445) + 1 → 1335 + 1 = 1336

## Step *42* of 111 → n = 1336

Since 1336 is even, we divide by 2 to get 1336 ÷ 2 = 668

## Step *43* of 111 → n = 668

Since 668 is even, we divide by 2 to get 668 ÷ 2 = 334

## Step *44* of 111 → n = 334

Since 334 is even, we divide by 2 to get 334 ÷ 2 = 167

## Step *45* of 111 → n = 167

Since 167 is odd, we take 3(167) + 1 → 501 + 1 = 502

## Step *46* of 111 → n = 502

Since 502 is even, we divide by 2 to get 502 ÷ 2 = 251

## Step *47* of 111 → n = 251

Since 251 is odd, we take 3(251) + 1 → 753 + 1 = 754

## Step *48* of 111 → n = 754

Since 754 is even, we divide by 2 to get 754 ÷ 2 = 377

## Step *49* of 111 → n = 377

Since 377 is odd, we take 3(377) + 1 → 1131 + 1 = 1132

## Step *50* of 111 → n = 1132

Since 1132 is even, we divide by 2 to get 1132 ÷ 2 = 566

## Step *51* of 111 → n = 566

Since 566 is even, we divide by 2 to get 566 ÷ 2 = 283

## Step *52* of 111 → n = 283

Since 283 is odd, we take 3(283) + 1 → 849 + 1 = 850

## Step *53* of 111 → n = 850

Since 850 is even, we divide by 2 to get 850 ÷ 2 = 425

## Step *54* of 111 → n = 425

Since 425 is odd, we take 3(425) + 1 → 1275 + 1 = 1276

## Step *55* of 111 → n = 1276

Since 1276 is even, we divide by 2 to get 1276 ÷ 2 = 638

## Step *56* of 111 → n = 638

Since 638 is even, we divide by 2 to get 638 ÷ 2 = 319

## Step *57* of 111 → n = 319

Since 319 is odd, we take 3(319) + 1 → 957 + 1 = 958

## Step *58* of 111 → n = 958

Since 958 is even, we divide by 2 to get 958 ÷ 2 = 479

## Step *59* of 111 → n = 479

Since 479 is odd, we take 3(479) + 1 → 1437 + 1 = 1438

## Step *60* of 111 → n = 1438

Since 1438 is even, we divide by 2 to get 1438 ÷ 2 = 719

## Step *61* of 111 → n = 719

Since 719 is odd, we take 3(719) + 1 → 2157 + 1 = 2158

## Step *62* of 111 → n = 2158

Since 2158 is even, we divide by 2 to get 2158 ÷ 2 = 1079

## Step *63* of 111 → n = 1079

Since 1079 is odd, we take 3(1079) + 1 → 3237 + 1 = 3238

## Step *64* of 111 → n = 3238

Since 3238 is even, we divide by 2 to get 3238 ÷ 2 = 1619

## Step *65* of 111 → n = 1619

Since 1619 is odd, we take 3(1619) + 1 → 4857 + 1 = 4858

## Step *66* of 111 → n = 4858

Since 4858 is even, we divide by 2 to get 4858 ÷ 2 = 2429

## Step *67* of 111 → n = 2429

Since 2429 is odd, we take 3(2429) + 1 → 7287 + 1 = 7288

## Step *68* of 111 → n = 7288

Since 7288 is even, we divide by 2 to get 7288 ÷ 2 = 3644

## Step *69* of 111 → n = 3644

Since 3644 is even, we divide by 2 to get 3644 ÷ 2 = 1822

## Step *70* of 111 → n = 1822

Since 1822 is even, we divide by 2 to get 1822 ÷ 2 = 911

## Step *71* of 111 → n = 911

Since 911 is odd, we take 3(911) + 1 → 2733 + 1 = 2734

## Step *72* of 111 → n = 2734

Since 2734 is even, we divide by 2 to get 2734 ÷ 2 = 1367

## Step *73* of 111 → n = 1367

Since 1367 is odd, we take 3(1367) + 1 → 4101 + 1 = 4102

## Step *74* of 111 → n = 4102

Since 4102 is even, we divide by 2 to get 4102 ÷ 2 = 2051

## Step *75* of 111 → n = 2051

Since 2051 is odd, we take 3(2051) + 1 → 6153 + 1 = 6154

## Step *76* of 111 → n = 6154

Since 6154 is even, we divide by 2 to get 6154 ÷ 2 = 3077

## Step *77* of 111 → n = 3077

Since 3077 is odd, we take 3(3077) + 1 → 9231 + 1 = 9232

## Step *78* of 111 → n = 9232

Since 9232 is even, we divide by 2 to get 9232 ÷ 2 = 4616

## Step *79* of 111 → n = 4616

Since 4616 is even, we divide by 2 to get 4616 ÷ 2 = 2308

## Step *80* of 111 → n = 2308

Since 2308 is even, we divide by 2 to get 2308 ÷ 2 = 1154

## Step *81* of 111 → n = 1154

Since 1154 is even, we divide by 2 to get 1154 ÷ 2 = 577

## Step *82* of 111 → n = 577

Since 577 is odd, we take 3(577) + 1 → 1731 + 1 = 1732

## Step *83* of 111 → n = 1732

Since 1732 is even, we divide by 2 to get 1732 ÷ 2 = 866

## Step *84* of 111 → n = 866

Since 866 is even, we divide by 2 to get 866 ÷ 2 = 433

## Step *85* of 111 → n = 433

Since 433 is odd, we take 3(433) + 1 → 1299 + 1 = 1300

## Step *86* of 111 → n = 1300

Since 1300 is even, we divide by 2 to get 1300 ÷ 2 = 650

## Step *87* of 111 → n = 650

Since 650 is even, we divide by 2 to get 650 ÷ 2 = 325

## Step *88* of 111 → n = 325

Since 325 is odd, we take 3(325) + 1 → 975 + 1 = 976

## Step *89* of 111 → n = 976

Since 976 is even, we divide by 2 to get 976 ÷ 2 = 488

## Step *90* of 111 → n = 488

Since 488 is even, we divide by 2 to get 488 ÷ 2 = 244

## Step *91* of 111 → n = 244

Since 244 is even, we divide by 2 to get 244 ÷ 2 = 122

## Step *92* of 111 → n = 122

Since 122 is even, we divide by 2 to get 122 ÷ 2 = 61

## Step *93* of 111 → n = 61

Since 61 is odd, we take 3(61) + 1 → 183 + 1 = 184

## Step *94* of 111 → n = 184

Since 184 is even, we divide by 2 to get 184 ÷ 2 = 92

## Step *95* of 111 → n = 92

Since 92 is even, we divide by 2 to get 92 ÷ 2 = 46

## Step *96* of 111 → n = 46

Since 46 is even, we divide by 2 to get 46 ÷ 2 = 23

## Step *97* of 111 → n = 23

Since 23 is odd, we take 3(23) + 1 → 69 + 1 = 70

## Step *98* of 111 → n = 70

Since 70 is even, we divide by 2 to get 70 ÷ 2 = 35

## Step *99* of 111 → n = 35

Since 35 is odd, we take 3(35) + 1 → 105 + 1 = 106

## Step *100* of 111 → n = 106

Since 106 is even, we divide by 2 to get 106 ÷ 2 = 53

## Step *101* of 111 → n = 53

Since 53 is odd, we take 3(53) + 1 → 159 + 1 = 160

## Step *102* of 111 → n = 160

Since 160 is even, we divide by 2 to get 160 ÷ 2 = 80

## Step *103* of 111 → n = 80

Since 80 is even, we divide by 2 to get 80 ÷ 2 = 40

## Step *104* of 111 → n = 40

Since 40 is even, we divide by 2 to get 40 ÷ 2 = 20

## Step *105* of 111 → n = 20

Since 20 is even, we divide by 2 to get 20 ÷ 2 = 10

## Step *106* of 111 → n = 10

Since 10 is even, we divide by 2 to get 10 ÷ 2 = 5

## Step *107* of 111 → n = 5

Since 5 is odd, we take 3(5) + 1 → 15 + 1 = 16

## Step *108* of 111 → n = 16

Since 16 is even, we divide by 2 to get 16 ÷ 2 = 8

## Step *109* of 111 → n = 8

Since 8 is even, we divide by 2 to get 8 ÷ 2 = 4

## Step *110* of 111 → n = 4

Since 4 is even, we divide by 2 to get 4 ÷ 2 = 2

## Step *111* of 111 → n = 2

Since 2 is even, we divide by 2 to get 2 ÷ 2 = 1

## Collatz Conjecture Video

## Tags:

**Add This Calculator To Your Website**